Simulating soil organic carbon in yedoma deposits during the Last Glacial Maximum in a land surface model. Issue 10 (21st May 2016) - Zhu, D.; Peng, S.; Ciais, P.; Zech, R.; Krinner, G.; Zimov, S.; Grosse, G.
Abstract: Substantial quantities of organic carbon (OC) are stored in the thick, ice‐rich, and organic‐rich sediments called yedoma deposits, distributed in eastern Siberia and Alaska today. Quantifying yedoma carbon stocks during the glacial period is important for understanding how much carbon could have been decomposed during the last deglaciation. Yet processes that yield the formation of thick frozen OC in yedoma deposits are missing in global carbon cycle models. Here we incorporate sedimentation parameterizations into the Organizing Carbon and Hydrology In Dynamic Ecosystems (ORCHIDEE‐MICT) land surface model, which leads to reasonable results in OC vertical distribution and regional budgets, compared with site‐specific observations and inventories for today's nondegraded yedoma region. Simulated total soil OC stock for the northern permafrost region during the Last Glacial Maximum (LGM) is 1536–1592 Pg C, of which 390–446 Pg C is within today's yedoma region. This result is an underestimation since we did not account for the potentially much larger yedoma area during the LGM than the present day. Key Points: A sedimentation parameterization in a large‐scale land surface model can simulate the buildup of deep carbon in yedoma Model results are evaluated against site measurements and regional inventories Simulated total soil organic carbon at the LGM is 390‐446 Pg C within today's yedoma region